Dual purpose microalgae-bacteria-based systems that treat wastewater and produce biodiesel and chemical products within a biorefinery - Eugenia Judith Olguín Palacios (Biotechnology Advances, 2012)
Excess greenhouse gas emissions and the concomitant effect on global warming have become significant en- vironmental, social and economic threats. In this context, the development of renewable, carbon-neutral and economically feasible biofuels is a driving force for innovation worldwide. A lot of effort has been put into de- veloping biodiesel from microalgae. However, there are still a number of technological, market and policy barriers that are serious obstacles to the economic feasibility and competitiveness of such biofuels. Converse- ly, there are also a number of business opportunities if the production of such alternative biofuel becomes part of a larger integrated system following the Biorefinery strategy. In this case, other biofuels and chemical products of high added value are produced, contributing to an overall enhancement of the economic viability of the whole integrated system. Additionally, dual purpose microalgae?bacteria-based systems for treating wastewater and production of biofuels and chemical products significantly contribute to a substantial saving in the overall cost of microalgae biomass production. These types of systems could help to improve the com- petitiveness of biodiesel production from microalgae, according to some recent Life Cycle Analysis studies. Furthermore, they do not compete for fresh water resources for agricultural purposes and add value to treating the wastewater itself. This work reviews the most recent and relevant information about these types of dual purpose systems. Several aspects related to the treatment of municipal and animal wastewater with simultaneous recovery of microalgae with potential for biodiesel production are discussed. The use of pre-treated waste or anaerobic effluents from digested waste as nutrient additives for weak wastewater is reviewed. Isolation and screening of microalgae/cyanobacteria or their consortia from various wastewater streams, and studies related to population dynamics in mixed cultures, are highlighted as very relevant fields of research. The species selection may depend on various factors, such as the biomass and lipid productivity of each strain, the characteristics of the wastewater, the original habitat of the strain and the climatic condi- tions in the treatment plant, among others. Some alternative technologies aimed at harvesting biomass at a low cost, such as cell immobilization, biofilm formation, flocculation and bio-flocculation, are also reviewed. Finally, a Biorefinery design is presented that integrates the treatment of municipal wastewater with the re- covery of oleaginous microalgae, together with the use of seawater supplemented with anaerobically digested piggery waste for cultivating Arthrospira (Spirulina) and producing biogas, biodiesel, hydrogen and other high added value products. Such strategies offer new opportunities for the cost-effective and com- petitive production of biofuels along with valuable non-fuel products.